E-037 Endovascular treatment of traumatic pediatric posterior circulation pseudoaneurysms. (16th November 2010) - Farid, H; Tatum, J; Halbach, V; Higashida, R; Dowd, C
Abstract : Introduction and purpose: Traumatic intracranial aneurysms are rare and represent fewer than 1% of all intracranial aneurysms. They may develop as the result of blunt or penetrating head trauma and are associated with a significant mortality of up to 50%. Traumatic aneurysms typically involve the anterior circulation or the internal carotid artery at the level of the skull base. They rarely involve the posterior circulation. We present three pediatric patients with traumatic aneurysms in the posterior circulation and describe their clinical presentation, angiographic findings and clinical outcome after being treated by endovascular technique. Materials and methods: We retrospectively reviewed the angiographic and clinical findings in three pediatric patients, aged 12 years and younger, with traumatic pseudoaneurysms occurring in the posterior circulation in a variety of locations: one in the basilar artery, one in the posterior cerebral artery and one in the superior cerebellar artery. Results: Three patients with three posterior circulation pseudoaneurysms (two male patients and one female patient; aged 3–12 years) were admitted during the past 2 years. All three patients underwent endovascular coil embolization. No complications were noted from these procedures. All patients improved clinically after treatment. Conclusions: Contemporary endovascular techniques can be used effectively to treat posterior circulation pseudoaneurysms in the pediatric population. Treatment efficacy may be improved if there are bony confines around the aneurysm or if therapy takes place in the subacute period, when the wall of the pseudoaneurysm has matured and stabilized.